2019
DOI: 10.1136/openhrt-2019-001088
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive intraventricular pressure differences estimated with cardiac MRI in subjects without heart failure and with heart failure with reduced and preserved ejection fraction

Abstract: ObjectiveNon-invasive assessment of left ventricular (LV) diastolic and systolic function is important to better understand physiological abnormalities in heart failure (HF). The spatiotemporal pattern of LV blood flow velocities during systole and diastole can be used to estimate intraventricular pressure differences (IVPDs). We aimed to demonstrate the feasibility of an MRI-based method to calculate systolic and diastolic IVPDs in subjects without heart failure (No-HF), and with HF with reduced ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Therefore, CMME-derived indices can non-invasively evaluate heart function. Studies revealed that the IVPD and IVPG as novel echocardiographic indices could reflect the diastolic function changes that could differentiate subtypes of heart failure ( 13 ). In addition, CMME variables showed more advantages regarding repeatability and continuous data acquisition for better interpretation of the segmental pressure ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CMME-derived indices can non-invasively evaluate heart function. Studies revealed that the IVPD and IVPG as novel echocardiographic indices could reflect the diastolic function changes that could differentiate subtypes of heart failure ( 13 ). In addition, CMME variables showed more advantages regarding repeatability and continuous data acquisition for better interpretation of the segmental pressure ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%